implementasi Implementasi Metode Insya’ Dalam Pengembangan Maharah Kitabah Mahasantri - Sholihah, Hajar; fanani, zahrodin (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
Purpose- Mastering Arabic writing skills (maharah kitabah) remains a major challenge in Arabic language learning. This study aims to examine the implementation of the insya’ method in developing the writing skills of third-semester students at Ma’had ‘Aly Mohammad Natsir Kartasura. Design/Methodology/Approach- This study employs a qualitative descriptive approach, utilizing classroom observation, open-ended questionnaires, and documentation as data collection techniques. The participants of this study are third-semester students at Ma’had ‘Aly Mohammad Natsir Kartasura. Findings- The findings reveal that the systematic and continuous implementation of the insya’ method enhances students’ accuracy in i’rab, vocabulary mastery, and their ability to construct Arabic sentences effectively. In addition, the method positively influences non-linguistic aspects, including motivation, writing habits, and students’ self-confidence. Research Limitations/Implications- This study is limited in terms of the number of participants and its localized scope. However, the findings provide valuable insights for the development of Arabic writing instruction strategies in similar educational contexts. Keywords: Arabic writing skills, insya’ method, Arabic language learning